Analisis Perbandingan Tingkat Depresi pada Mahasiswa Angkatan 2022 dan 2024 Jurusan Biologi Universitas Negeri Medan - Findi Septiani; Endang Lyfia Saragih; Grace Amelia Purba; Petra Putri Sarinah Pandiangan; Rizka Nabila Damanik (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
Mental health disorders, particularly depression, are becoming an increasing concern among university students. This study aims to analyze the comparative levels of depression among students from the 2022 and 2024 cohorts in the Biology Department at Universitas Negeri Medan. The research employs a mixed-method approach, integrating both quantitative and qualitative methodologies. Data were collected through questionnaires distributed to 51 active students. The results indicate that students from the 2022 cohort exhibit higher levels of depression compared to those from the 2024 cohort, due to academic pressure, social factors, and lifestyle habits. These findings highlight the importance of preventive strategies and interventions to mitigate depression risks, such as stress management, promoting healthy lifestyle habits, and strengthening social support in academic environments. Therefore, educational institutions must prioritize student mental health to foster a more conducive learning environment.